Ética, justiça e educação no pensamento de Paul Ricoeur - RIBEIRO, Lúcia de Fátima (2011)
The aim of this work is to examine in Paul Ricoeur the notions of ethics and justice and their pedagogical implications. The theoretical referential is the phenomenological hermeneutic and the methodology is basead on the bibliographic research of the author work and his commentors. Initially, it seeks to explain what ethics is for the author, the principles that guide it and its applicability and present. This work was prepared on the basis of reflection on the human act, wondering if this is an essential way of being and trying to understand the man in the world today. Then, the theme of justice was discussed that, for Ricoeur, is part of the desire to live well. The fair is no longer good, nor even legal, but equitable. To mark where question of justice can be found, it was made a distinction between the notion of another and another. Ricoeur takes the Aristotelian definition of friendship in order to specify the vality and scope of solicitude. For him, the friendship anticipates the solicitude, facilitating good perspective on good life, rooted in self-esteem; the justice is taken at the institutional level as a political virtue. These discussions evidence the many implications of ricoeuriana ethics and justice in the field of education. Finally, it seeks to explain these implications. Education as enriches itself and promotes a sensible human action in the sense the person reaches the self knowledge truth and of self identity recognition. So, it can be said that the Ricoeur‟s ethical proposal because of a good and in harmony life for everyone, also guided by justice is possible and can be the way of the today world for a fair distribution of goods in short and long times. And, yet, it may be the pillar which warrants the discussion progress about the occidental ethics and the gaps, in the advance of discussion, that are still breakpoints to search for a humanitarian and egalitarian society and overall a man more humanized